ON A MATHEMATICAL PAPER OF MILUTIN MILANKOVIĆ IN THE CONTEXT OF THE NEWER DIFFERENTIAL CALCULUS PAPERS - Malešević, Jovan V. (Matematichki Bilten, 2008)
According to the paper [2] by Jovan Karamata, the paper [1] by Milutin Milanković „has entered many textbooks with certain changes“. In the context of the papers listed in references, the author gave an analogon to the mentioned paper of Milutin Milanković in Differential calculus as well as the numerous correlaries of the analogon. Therefore, the paper is an overview of analogon and correlaries, published in the year of the 100th anniversary of Milutin Milanković’s paper [1] in 1909.